Supporting National Food Security Through the Implementation of Radio Frequency Identification (RFID) in the Warehouses of Badan Urusan Logistik - Fatimatuz Zahroh; Najma Sekar Langit; Steven Julianto Situmeang; Hanissa Okitasari (Universitas Pendidikan Indonesia, 2023)
As many as 20,000 tons of rice in 2019 were discarded from the Logistics Agency (BULOG) warehouses due to their declining quality, making them unfit for consumption. The cause of rice damage is that the storage owned by BULOG is not a special warehouse for storing rice. This study aims to analyze BULOG rice storage and formulate ways to improve rice quality in realizing food security The method used in this research is qualitative approach and data collection using Focus Group Discussion (FGD) involving 15 people in the Edu Logistics Hub community. The application of Radio Frequency Identification (RFID) which processes information from rice stored in warehouses can minimize human error. The decline in the quality of rice in BULOG warehouses can be overcome by applying the First In First Out (FIFO) method and the application of RFID technology.